Effect of Heat Treatment on Some Thermodynamics Analysis, Crystal and Microstructures of Cu-Al-X (X: Nb, Hf) Shape Memory Alloy - Öner, Ecem Özen; Ateş, Gonca; Mohammed, Safar Saeed; Kanca, Muhammed; Kök, Mediha (Niyazi BULUT, 2024)
Heat treatment is an important technique that can improve the properties of shape memory alloys. In this study the effect of heat treatment at three different temperatures (973 K, 1073 K and 1173 K) on some thermodynamics parameters, crystal structure, and microstructure of Cu_86 Al_12 Nb_2 and Cu_86 Al_12 Hf_2 (mass %) Shape Memory Alloy has been investigated. After heat treatment, the change in the thermal properties of the samples was determined using Differential Scanning calorimetry (DSC). The effect of heat treatment on the crystal and microstructure of the alloy samples were determined at room temperature using X-ray diffraction (XRD), Scanning Electron microscopy (SEM) device. The DSC result showed that in both samples the temperature hysteresis was decreased after heat treatment. Also grain size was decreased by increasing the treatment temperature in both samples. And finally, optical images represented that Hafnium (Hf) is more dissolved in the alloy compared to Niobium (Nb).
Keywords: Materials Engineering (Other); Malzeme Mühendisliği (Diğer)